Cardiac metastasis of oral squamous cell carcinoma. (9th September 2015) - Pattni, Neeraj; Rennie, Andrew; Hall, Timothy; Norman, Aidan
Abstract : We present a case of isolated cardiac metastasis of oral squamous cell carcinoma. An 89-year-old woman was due to undergo curative resection of a histologically proven squamous cell carcinoma of the retromolar region. On admission, it was noted that there were ECG changes, and following further investigations, the patient was diagnosed with a cardiac metastasis of her oral malignancy. The presentation, including the diagnostic difficulties, as well as the clinical features of this rare case, are discussed.